Markers of Cardiac Autonomic Function During Consecutive Day Peak Exercise Tests in People With Myalgic Encephalomyelitis/Chronic Fatigue Syndrome - Nelson, Maximillian J.; Buckley, Jonathan D.; Thomson, Rebecca L.; Bellenger, Clint R.; Davison, Kade (Frontiers in Physiology, 2021)
Patients with Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) have been shown to exhibit altered ventilatory characteristics on the second of two progressive maximal exercise tests (CPET) performed on consecutive days. However, maximal exercise can exacerbate symptoms for ME/CFS patients and cause significant post-exertional malaise. Assessment of heart rate (HR) parameters known to track post-exertional fatigue may represent more effective physiological markers of the condition and could potentially negate the need for maximal exercise testing. Sixteen ME/CFS patients and ten healthy controls underwent a sub-maximal warm-up followed by CPET on two-consecutive days. Ventilation, ratings of perceived exertion (RPE), work rate (WR) and HR parameters were assessed throughout on both days. During sub-maximal warm-up, a time effect was identified for steady-state HR (p=0.03) and the ratio of low frequency to high frequency power of HR variability (p=0.02) with both being higher on Day Two of testing. A significant group (p<0.01) effect was identified for a lower post-exercise HR recovery (HRR) in ME/CFS patients. ROC curve analysis of HRR revealed an area under the curve of 74.8 % (p=0.02) on Day One of testing, with a HRR of 34.5 bpm maximising sensitivity (63%) and specificity (40%) suggesting while HRR values are altered in ME/CFS patients, low sensitivity and specificity limit its potential usefulness as a biomarker of the condition.